Fixed Point Theorems on Some New Types of Cyclic Contractions and Their Generalization - Joshi, Dev Raj; Tripathi, Piyush Kumar; Bhatta, Chet Raj (Journal of Nepal Mathematical Society, 2021)
There are different types of contraction in the existing literature for the generalization of Banach’s contraction principle. Our aim in this paper is to generalize cyclic contraction so that it can explain all types of cyclic contraction as a particular case. Besides all contractions in the existing literature we introduce some new types of cyclic contraction before defining the generalized cyclic contraction.